PENGARUH KARAKTERISTIK GOOD CORPORATE GOVERNANCE (GCG) TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI INDONESIA (Studi Empiris Pada Perusahaan perbankan Yang Terdaftar di BEI Tahun 2008-2011) - Dwi Arini Untoro; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
This study aimed to analyze the characteristics of the GCG that affect CSR disclosure in annual reports of banking companies listed in the Indonesian Stock Exchange in the year 2008-2011. GCG characteristics used in this study is the size of the board of commissioners, the proportion of independent of commissioners, and audit committee size.The population of this study are all banking companies listed on the Indonesia Stock Exchange (BEI) in the year 2008-2011. Total sample is 100 annual report of banking companies as determined by purposive sampling method. This research analyzes CSR disclosure in annual reports by the method of content analysis. Data analysis was performed using multiple regression analysis with SPSS for Windows 16.00.The results of this study indicate that the size of the board of directors and firm size (size) significantly affect CSR disclosure in Indonesia, and the proportion of independent board of directors, audit committee size, leverage, and profitability no proven effect against broad disclosure of CSR.